2021
DOI: 10.1101/2021.01.27.21250559
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

New-Onset IgG Autoantibodies in Hospitalized Patients with COVID-19

Abstract: Coronavirus Disease 2019 (COVID-19), caused by Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2), is associated with a wide range of clinical manifestations, including autoimmune features and autoantibody production. We developed three different protein arrays to measure hallmark IgG autoantibodies associated with Connective Tissue Diseases (CTDs), Anti-Cytokine Antibodies (ACA), and anti-viral antibody responses in 147 hospitalized COVID-19 patients in three different centers. Autoantibodies were i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
41
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 56 publications
1
41
0
4
Order By: Relevance
“…In this context, the inflammatory monocytes have been shown to promote the differentiation of naïve B cells into plasmablasts which can be the source of protective or pathogenic antibodies. In this regard we note that severe COVID-19 has been associated with various types of autoantibodies[31][32][33] .Our study highlights the importance of analyzing the initial immune state of COVID-19 patients early in their ICU course by deconvolution of genomic states of peripheral immune cells based on gene modules. Earlier work in non-COVID ARDS has defined monocyte signatures in PBMC that are indicative of progression to ARDS 34 ; our work demonstrates distinctive monocyte gene modules as part of a multivariate peripheral immune system state that is predictive of severe COVID-19 disease mortality.…”
mentioning
confidence: 63%
“…In this context, the inflammatory monocytes have been shown to promote the differentiation of naïve B cells into plasmablasts which can be the source of protective or pathogenic antibodies. In this regard we note that severe COVID-19 has been associated with various types of autoantibodies[31][32][33] .Our study highlights the importance of analyzing the initial immune state of COVID-19 patients early in their ICU course by deconvolution of genomic states of peripheral immune cells based on gene modules. Earlier work in non-COVID ARDS has defined monocyte signatures in PBMC that are indicative of progression to ARDS 34 ; our work demonstrates distinctive monocyte gene modules as part of a multivariate peripheral immune system state that is predictive of severe COVID-19 disease mortality.…”
mentioning
confidence: 63%
“…Third, multiple studies, including autopsy studies, have demonstrated endotheliitis and microvascular thrombosis in acute COVID-19, with neutrophil extracellular traps as one contributing mechanism [39][40][41][42][43][44]; in addition to explaining severe disease, ongoing microvascular dysfunction may contribute to the pathobiology of PASC. Fourth, autoreactive immunity may be a significant contributor as IgG autoantibodies are highly prevalent in acute infection, including those associated with clinical disease entities similar to PASC [39,[45][46][47]. Importantly, some mechanisms may contribute to certain organ-specific morbidity, whereas others might be common among various PASC phenotypes.…”
Section: There Are Multiple Mechanisms That Might Contribute To Pascmentioning
confidence: 99%
“…It is apparent from multiple studies that some COVID-19 patients have autoantibodies against a diverse range of self-antigens beyond type I interferons, and that these autoantibodies can have both short-and long-term pathogenic consequences [12,23,[26][27][28][29]. Thus, there is already some debate as to whether individuals with pre-existing subclinical autoimmune conditions are more likely to develop severe COVID-19, or whether severe SARS-CoV-2 infections trigger de novo autoreactivity against various antigens [12,30].…”
Section: Do Anti-interferon Autoantibodies Pre-exist In Virus-susceptible Individuals?mentioning
confidence: 99%
“…Thus, there is already some debate as to whether individuals with pre-existing subclinical autoimmune conditions are more likely to develop severe COVID-19, or whether severe SARS-CoV-2 infections trigger de novo autoreactivity against various antigens [12,30]. Longitudinal analyses of autoantibody reactivity in COVID-19 patient cohorts have indicated that both mechanisms may actually apply, but perhaps in an antigen-dependent manner [23,29]. Specifically, autoantibodies targeting type I interferons were found to pre-exist in several individuals who went on to develop severe COVID-19 [12,23], suggesting that the SARS-CoV-2 infection itself did not drive the primary production of anti-interferon autoantibodies.…”
Section: Do Anti-interferon Autoantibodies Pre-exist In Virus-susceptible Individuals?mentioning
confidence: 99%
See 1 more Smart Citation